Molecular identification of the emerging Human Gemykibivirus-2 (HuGkV-2) among Brazilian blood donors. (February 2023) - Zucherato, Victória Simionatto; Giovanetti, Marta; Costa, Lara Okuyama Afonso; Krause, Luciana Maria Fontanari; Alves, Daiani Cristina Cilião; Moreira, Renata Maria Alencar; Pimentel, Barbara Maciel Sidou; Haddad, Rodrigo; Bitencourt, Hellen Tayaná; Ciccozzi, Massimo; Alcantara, Luiz Carlos Júnior; Kashima, Simone; et al.
Abstract: Human gemykibivirus-2 (HuGkV-2) belonging to the Gemykibivirus genus (Genomoviridae family) is an emerging DNA virus which has been described as a component of the virome of a wide variety of samples including clinical ones. So far, the HuGkV-2 DNA prevalence in the human population as well as its clinical impact are completely unknown. The objective of this study was to investigate the HuGkV-2 DNA prevalence among Brazilian healthy blood donors from three different geographic regions. A total of 450 blood samples were screened for HuGkV-2 DNA (150 samples were from the Brazilian Amazon, 150 from Midwest Brazil and 150 from South Brazil). The overall HuGkV-2 DNA prevalence was 7.8 %. Considering the examined regions, the highest prevalence was observed in the Brazilian Amazon (city of Macapa, state of Amapa), 15.3 %, followed by the Midwest Brazil (city of Brasilia, Federal District) (6.0 %) and South Brazil (city of Santa Maria, Rio Grande do Sul State) (2.0 %). This study gives preliminary insights on the molecular prevalence of HuGkV-2 DNA among Brazilian blood donors, highlighting that the highest HuGkV-2 prevalence was recorded in the Brazilian Amazon. However, more studies regarding the prevalence, transmission routes and any possible clinical effects appear to be crucial in order to understand the impact of this emerging viral agent. Highlights: Human gemykibivirus-2 (HuGkV-2) is an emerging virus discovered by metagenomics. HuGkV-2 DNA prevalence was estimated in Brazilian blood donors from three regions (Amazon, Central-West and South). The Higher ighest HuGkV-2 DNA prevalence was estimated in the Brazilian Amazon, More studies are needed to examine HuGkV-2 clinical significance and, transmission routes